Direct manipulation of tool‐like masters for controlling a master–slave surgical robotic system. Issue 4 (11th October 2013) - Zhang, Linan; Zhou, Ningxin; Wang, Shuxin
Abstract Background Robotic‐assisted minimally invasive surgery (MIS) can benefit both patients and surgeons. However, the learning curve for robotically assisted procedures can be long and the total system costs are high. Therefore, there is considerable interest in new methods and lower cost controllers for a surgical robotic system. Methods In this study, a knife‐master and a forceps‐master, shaped similarly to a surgical knife and forceps, were developed as input devices for control of a master–slave surgical robotic system. In addition, a safety strategy was developed to eliminate the master–slave orientation difference and stabilize the surgical system. Results Master–slave tracking experiments and a ring‐and‐bar experiment showed that the safety tracking strategy could ensure that the robot system moved stably without any tremor in the tracking motion. Subjects could manipulate the surgical tool to achieve the master–slave operation with less training compared to a mechanical master. Conclusions Direct manipulation of the small, light and low‐cost surgical tools to control a robotic system is a possible operating mode. Surgeons can operate the robotic system in their own familiar way, without long training. The main potential safety issues can be solved by the proposed safety control strategy. Copyright © 2013 John Wiley & Sons, Ltd.